Agricultural Product Prices - William G. Tomek, Harry M. Kaiser (Cornell University Press, 2014)
The fi fth edition, of course, updates tables and fi gures from the fourth edition, and as noted below, addresses the effects of changes in markets for agricultural products. The organizational structure of the fi fth edition is similar to the fourth, but one organizational change was to move the material on tariffs and prices, previously in the appendix to Chapter 11 , to an expanded section on spatial price relationships and trade policy in Chapter 8 . A section on domestic agricultural policy is, however, retained in Chapter 11 as part of the discussion of administered prices. A major challenge for authors of textbooks in applied economics is the growing complexity and diversity of the worldwide economy. The fi fth edition discusses the nature of this increased complexity and its effects on price behavior, but without greatly lengthening the book. For example, we discuss the increased diversity of the derived demands for commodities, including both new sources of demand and changes in demands for attributes (e.g., in Chapters 2 and 7 ). Likewise, Chapters 5 , 6 , 11 , and 12 convey the changing nature of the structure of agricultural markets and pricing institutions. One example is the increased diversity of contracts offered by buyers to farmers. Nonetheless, the fi fth edition continues to emphasize the use of basic economic models to provide an understanding of the behavior of agricultural product prices and of the consequences of this behavior. Thus, this edition is still appropriate for upper-division courses in agricultural markets and prices. Like past editions, the book has suffi cient breadth to give teachers fl exibility in the choice of topics for their particular course. The references provide more depth and perhaps make the book useful for masters-degree courses. Graduate students have also indicated that the book is useful background for research and for preparing for examinations, and we hope that this remains true. Indeed, if carefully read, the book implies subjects where additional research would be valuable.